Citation pattern of open access and toll-based research articles in the field of biological and physical sciences: a comparative study - Wani, Zahid Ashraf; Shah, Tariq Shafi (Online information review, 2023)
PurposeThe purpose of this paper is to determine the relationship between the access mode of research articles [Open Access (OA) and Toll-Access (TA)] and their subsequent citation counts in Biological and Physical Sciences in three Impact factor zones (High, Medium and Low).Design/methodology/approachThree subjects each from Biological Sciences (Biochemistry, Cell Biology and Genetics) and Physical Sciences (Astronomy, Oceanography and Optics) were selected for the study. A comprehensive list of journals (TA and OA) in select subjects of Biological and Physical Sciences was prepared by consulting Journal Citation Report’s Master Journal List (for the compilation of both Open Access and Toll Access journal list) and Directory of Open Access Journals (for the compilation of Open Access journal list). For each journal, essential details like content language, format, year of publication, access mode (Open Access or Toll Access), etc. were obtained from Ulrich’s Periodical Directory. Web of Science (WoS) was used as citations indexing tool in this study. The data set was run on the WoS to collect the citation data.FindingsThe results of the study indicate that open mode of access is not a prerequisite for higher citation boost as in the majority of the cases in this study, TA articles have garnered a greater number of citations as compared to open access articles in different Impact factor zones in Biological and Physical Sciences.Originality/valueA novel approach has been adopted to understand and compare the research impact of open access (OA) and toll access (TA) journal articles in the field of Biological and Physical Sciences at three Impact factor zone levels to reveal the citation metrics encompassing three parameters, i.e. citedness, average citation count and year wise distribution of citations in select subjects of Biological and Physical Sciences.Peer reviewThe peer review history for this article is available at: https://publons.com/publon/[DOI]/10.1108/OIR-01-2021-0029